2012
DOI: 10.1139/x2012-034
|View full text |Cite
|
Sign up to set email alerts
|

A detrimental soil disturbance prediction model for ground-based timber harvesting

Abstract: Soil properties and forest productivity can be affected during ground-based harvest operations and site preparation. The degree of impact varies widely depending on topographic features and soil properties. Forest managers who understand site-specific limits to ground-based harvesting can alter harvest method or season to limit soil disturbance. To determine the potential areal extent of detrimental (potentially plant growth limiting) soil disturbance based on site characteristics and season of harvest, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Our results showed that forest sites with northeastern and eastern aspects are more exposed to damage than other aspects, probably due to microclimate-related conditions (Reeves et al 2012).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results showed that forest sites with northeastern and eastern aspects are more exposed to damage than other aspects, probably due to microclimate-related conditions (Reeves et al 2012).…”
Section: Discussionmentioning
confidence: 67%
“…Soil damage susceptibility can be provided using a number of different techniques such as linear re-gression (Singh, Kushwaha 2011), generalized additive models (Goetz et al 2011), frequency ratio model (Pourghasemi et al 2012a), neurofuzzy (Manel et al 1999) and tree-based methods (Cutler et al 2007). Despite the widespread use of these methods in other sciences, they have been only limited to a linear model which is performed to predict soil damage in forest ecosystems (Sowa, Kulak 2008;Reeves et al 2012).…”
mentioning
confidence: 99%
“…relevant (Reeves et al, 2012). Other studies acknowledge the importance of forest floor depth (all organic horizons), soil quantity of coarse fragments, and soil depth (Kimsey et al, 2011).…”
Section: Wwf Ca (2010)mentioning
confidence: 99%
“…For example, McMahon (1995) evaluated the 4 ha nearest the landing to estimate disturbance on a 26 ha site. Reeves et al (2012) walked line transects from stand boundary to boundary, perpendicular to skid trails. McNeel and Ballard (1992) laid out transects 4 m in width, at 20 m intervals across the entire stand, while Lanford and Stokes (1995) used a two-tier system, sampling disturbance perpendicularly to selected trails at 25 ft. (7.6 m) intervals, then systematically sampling stand-wise disturbance by installing 3 parallel lines across the site and evaluating conditions every 40 ft. (12 m) along these lines.…”
Section: Introductionmentioning
confidence: 99%